2013
DOI: 10.1097/mej.0b013e32835015ac
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medical service in the stroke chain of survival

Abstract: Our study demonstrates that public intervention programmes must stress the urgency of recognizing stroke symptoms and the importance of calling EMS through free telephone numbers. Further efforts are necessary to disseminate guidelines for healthcare providers concerning stroke recognition and the new therapeutic possibilities in order to increase the likelihood of acute stroke patients presenting to a stroke team early enough to be eligible for acute treatment. In addition, EMS dispatchers should receive furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 13 publications
5
23
1
Order By: Relevance
“…This is consistent with a previous study, which evaluated the impact of speech impairment on utility and found that the mean utility for major stroke reduced from 0.34 to 0.26 after speech deficits were considered [18]. Indeed, speech problems are common in stroke survivors [22,23], and they can significantly impair patients' communication and quality of life. Therefore, it is crucial to include speech deficits in the descriptions of post-stroke health states.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with a previous study, which evaluated the impact of speech impairment on utility and found that the mean utility for major stroke reduced from 0.34 to 0.26 after speech deficits were considered [18]. Indeed, speech problems are common in stroke survivors [22,23], and they can significantly impair patients' communication and quality of life. Therefore, it is crucial to include speech deficits in the descriptions of post-stroke health states.…”
Section: Discussionsupporting
confidence: 88%
“…This is comparable to previously presented data of correct prehospital identification of 42-57% [13,15,21,22]. To improve access to thrombolysis, fast identification of stroke is imperative, thus stroke patients not captured by the EMCC are a pressing concern.…”
Section: Discussionsupporting
confidence: 73%
“…Another study of emergency calls reports fall/collapse (26%) followed by stroke (25%) as the first problem presented by the caller and FAST symptoms to be initially presented in less than 5% [13]. Also, general discomfort, chest pain, dyspnea, fall or vertigo were the main symptoms expressed in misdiagnosed stroke patients according to Chenaitia et al [15]. As the FAST test mainly captures symptoms from the anterior circulation, not all stroke patients are expected to have a positive FAST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each county ( département ), a SAMU ( Service d’Aide Médicale Urgente ) call centre coordinates pre-hospital EMS 24/7. One or more on-duty physicians counsel callers, dispatch the fire brigade, an ambulance or a mobile intensive care unit on site, and enquire into bed availability in hospitals accepting stroke patients [24]. Hospital stroke units manage patients either autonomously or via a telemedicine link with other hospitals.…”
Section: Methodsmentioning
confidence: 99%